Safety assessment of essential medicines for elderly people: a bibliographic survey - Varallo, Fabiana Rossi [UNESP]; Oliveira, Fernanda Mariana de [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (Universidade de São Paulo, Conjunto Químicas, 2014)
Certain medicines are considered potentially inappropriate (PIM) for elderly people as they increase the risk of adverse drug events (ADE) and because safer alternative therapies are available on the market. In this context, in order to identify the instruments that assess the quality of medical prescriptions for elderly and to determine which drugs are considered PIM, a bibliographic survey was conducted in PUBMED, LILACS and PAHO databases, in February and March/2010. The search strategy included the use of health descriptors and a manual search in the references cited by selected papers. During the period of data collection, 15 instruments were identified. In 2012, with the publication of the update of Beers criteria, this instrument was included in the study. We identified 163 PIM of 25 therapeutic classes, of which 125 (76.7%) are marketed in Brazil. Of these, 31 (24.8%) are essential medicines (RENAME 2012), of which 13 have safer therapeutic equivalents and 19 (15.2%) are over-the-counter drugs. Data suggest the need for inclusion of safer alternatives for the elderly in the national list of essential medicines and the pharmaceutical care for early detection of ADE in this age group, in order to contribute to the safe use of medicines.

Determinados medicamentos são considerados potencialmente inapropriados (MPI) para idosos, por aumentarem o risco de ocorrência de eventos adversos a medicamentos (EAM) e por existirem alternativas terapêuticas mais seguras. Neste contexto, com o intuito de identificar os instrumentos que avaliam a qualidade das prescrições médicas para idosos e verificar quais medicamentos são considerados MPI, levantamento bibliográfico foi realizado nas bases de dados PUBMED, LILACS e PAHO em fevereiro e março de 2010. Para a seleção dos manuscritos utilizaram-se descritores em saúde e busca manual nas referências bibliográficas dos artigos identificados. No período da coleta de dados, foram identificados 15 instrumentos. Em 2012, com a publicação da atualização da lista de Beers, este instrumento foi incluído no estudo. Foram identificados 163 MPI de 25 classes terapêuticas, dos quais 125 (76,7%) são comercializados no Brasil. Destes, 31 (24,8%) são medicamentos essenciais (RENAME 2012), sendo que para 13 deles há equivalentes terapêuticos mais seguros e 19 (15,2%) são medicamentos isentos de prescrição. Os dados sugerem a necessidade de inclusão de medicamentos mais seguros para idosos na lista nacional de medicamentos essenciais e do monitoramento farmacoterapêutico para a detecção precoce de EAM nesta faixa etária para contribuir com o uso seguro de medicamentos.
Keywords: Aged/medicines prescription; Medication/errors; Medicines/inappropriate prescribing; Medicines/adverse effects/control; Medicines/safety use; Medication/risk assessment/control; Pharmaceutical care; Idoso/prescrição de medicamentos; Medicação/erros; Medicamentos/prescrição inadequada; Medicamentos/efeitos adversos/controle; Medicamentos/uso seguro; Medicação de risco/controle; Monitoramento farmacoterapêutico